2020
DOI: 10.1007/s10295-019-02242-x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of advanced producers of first- and second-generation ethanol in Saccharomyces cerevisiae and selected species of non-conventional yeasts (Scheffersomyces stipitis, Ogataea polymorpha)

Abstract: This review summarizes progress in the construction of efficient yeast ethanol producers from glucose/sucrose and lignocellulose. Saccharomyces cerevisiae is the major industrial producer of first-generation ethanol. The different approaches to increase ethanol yield and productivity from glucose in S. cerevisiae are described. Construction of the producers of secondgeneration ethanol is described for S. cerevisiae, one of the best natural xylose fermenters, Scheffersomyces stipitis and the most thermotolerant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 209 publications
(262 reference statements)
1
42
0
Order By: Relevance
“…This tolerance is close to the naturally occurring, wild-type strains of yeasts (up to 6% ethanol by certain species in the genus Saccharomyces , Candida , Fabospora , Kluyveromyces , Kloeckera ) and of specific filamentous fungi (3–7% by certain species in the genus Rhizopus and Fusarium ) used for producing ethanol and above the typical limits of alcohol tolerance in other fungal species ( Gao and Fleet, 1988 ; Singh and Kumar, 1991 ; Singh et al, 1992 ; Skory et al, 1997 ; Banat et al, 1998 ; Pina et al, 2004 ; Benjaphokee et al, 2012 ; Ferreira et al, 2014 ; Lam et al, 2014 ; Paschos et al, 2015 ; Ruchala et al, 2020 ). In biotechnology, ethanol tolerance and production of fungi can be increased by culture dependent methods (e.g., pH, temperature, medium, carbon-source), genetic modifications and artificial selection (e.g., Gao and Fleet, 1988 ; Skory et al, 1997 ; Pina et al, 2004 ; Benjaphokee et al, 2012 ; Lam et al, 2014 ; Ruchala et al, 2020 ). The extraordinary tolerance of some of our tested fungi in combination with the known ethanol production of ambrosia beetle fungi makes them quite interesting for biotechnological purposes (i.e., second-generation biofuels made from plant biomass).…”
Section: Discussionmentioning
confidence: 99%
“…This tolerance is close to the naturally occurring, wild-type strains of yeasts (up to 6% ethanol by certain species in the genus Saccharomyces , Candida , Fabospora , Kluyveromyces , Kloeckera ) and of specific filamentous fungi (3–7% by certain species in the genus Rhizopus and Fusarium ) used for producing ethanol and above the typical limits of alcohol tolerance in other fungal species ( Gao and Fleet, 1988 ; Singh and Kumar, 1991 ; Singh et al, 1992 ; Skory et al, 1997 ; Banat et al, 1998 ; Pina et al, 2004 ; Benjaphokee et al, 2012 ; Ferreira et al, 2014 ; Lam et al, 2014 ; Paschos et al, 2015 ; Ruchala et al, 2020 ). In biotechnology, ethanol tolerance and production of fungi can be increased by culture dependent methods (e.g., pH, temperature, medium, carbon-source), genetic modifications and artificial selection (e.g., Gao and Fleet, 1988 ; Skory et al, 1997 ; Pina et al, 2004 ; Benjaphokee et al, 2012 ; Lam et al, 2014 ; Ruchala et al, 2020 ). The extraordinary tolerance of some of our tested fungi in combination with the known ethanol production of ambrosia beetle fungi makes them quite interesting for biotechnological purposes (i.e., second-generation biofuels made from plant biomass).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide annual production is currently more than 100 billion L and it is expected to cross 134 billion L by 2024 [ 2 ]. Saccharomyces cerevisiae is the predominant organism used for bioethanol production and there is great interest in generating superior production strains [ 3 , 4 ] since merely a 1% increase in ethanol yield can already save the industry millions of dollars annually [ 5 ]. Some characteristics of S. cerevisiae that make it an ideal host for industrial production are efficient anaerobic ethanol production, tolerance to ethanol and other stress factors such as low pH as well as its insensitivity to bacteriophage infection.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most significant food and beverages known to humans (such as beer, wine, and bread) are made through the alcoholic fermentation process. These traditional fermentation products are produced by using yeast strains to spontaneously ferment carbon-rich substrates (e.g., bread/beer from cereals, wine from grapes) [36,[47][48][49]. Some studies have shown that despite many kinds of microbes involved in the brewing of wine and other fermentation production, S. cerevisiae has always been the dominant species [50][51][52].…”
Section: The Fungi and Their Potential In The Utilization Of Plant Pomentioning
confidence: 99%